How Customer Expectations Become Adjusted After Purchase. Issue 4 (1st October 2016) - Lin, Chinho; Lekhawipat, Watcharee
ABSTRACT: Adjusted expectations play an important role in the post-purchase process. By considering the changes in individual-level expectations in the post-purchase period, this study examines the moderating effects of the level of online shopping habit on the links between adjusted expectations and their antecedents. The study proposes a theoretical model by integrating the expectancy disconfirmation model and customer value dimensions to compare the factors affecting adjusted expectations between the low and high online shopping habit. The results indicate that the effects of expectancy disconfirmation on adjusted expectations are stronger for the high-habit group than for the low-habit group. Further, the level of online shopping habit moderates the links between customer value dimensions and adjusted expectations. Specifically, factors such as confidence benefits and perceived price are associated with adjusted expectations for the low-habit group. In addition, for the high-habit group, perceived equity has a positive influence on adjusted expectations, and perceived sacrifice has a negative impact. These findings provide a better understanding of how customer expectations change, and can assist practitioners in developing more effective online business strategies.